Energy Conservation and the Paradigm of Sustainable Economic Development: Examining the Status and Initiatives for Energy Conservation in India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Energy is the Life Blood of economy and Oxygen for the very existenceof mankind, therefore the entire universe is the manifestation of energy invarious forms. Energy plays a very crucial and pivotal role in the sustainabledevelopment of the economy. The present paper precisely provides the presentand future status of the potential of energy conservation, energy conservationstrategies and measures adopted by Government of India, corporate and societyas a whole.